2008
DOI: 10.1080/15564900802487634
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the September 11, 2001, Attacks on the Well-Being of Arab Americans in New York City

Abstract: In this exploratory study, eight focus groups were conducted, utilizing 83 participants. A structured, but flexible, interview guided by trauma theory was designed to solicit perspectives on the impact of the September 11, 2001, attacks on the Arab American community in New York City. Participants identified several common areas of concern, including fear of hate crimes, anxiety about the future, threats to their safety, loss of community, isolation, and stigmatization. Barriers to services and current mental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
78
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(81 citation statements)
references
References 14 publications
3
78
0
Order By: Relevance
“…This could be particularly true for Malays. In Islam, the religion practiced by the large majority of Malays in Singapore, mental illness is perceived as a test from God [32, 33], and illness could be treated as an opportunity to remedy disconnection from God or resolve a lack of faith through regular prayer and a sense of self-responsibility [34, 35]. Thus they were more tolerant to mental illness, as reported in other local studies as well [13, 21].…”
Section: Discussionmentioning
confidence: 91%
“…This could be particularly true for Malays. In Islam, the religion practiced by the large majority of Malays in Singapore, mental illness is perceived as a test from God [32, 33], and illness could be treated as an opportunity to remedy disconnection from God or resolve a lack of faith through regular prayer and a sense of self-responsibility [34, 35]. Thus they were more tolerant to mental illness, as reported in other local studies as well [13, 21].…”
Section: Discussionmentioning
confidence: 91%
“…This phenomenon only emerged in a condition where candidates had slightly negative profiles, which indicates that racism may increase scrutiny (Park et al, 2009). Additionally, research indicates that AMIs perceive disparities in mental health resources, such as a lack of facilities and services located in their communities (Abu-Ras & Abu-Bader, 2008), but no empirical analyses have attempted to substantiate this impression. Overall, the limited number of studies falls short of truly assessing the depth of institutional racism, but the existing evidence suggests that it exits and may be pernicious (Brown, 1998).…”
Section: Macrosystem Racismmentioning
confidence: 97%
“…Specific examples include physical assaults, arson of mosques, verbal assaults, bomb threats, and denial of services (CAIR, 2012;Edwards, 2010;Nadal et al, 2012;Rippy & Newman, 2006). AMIs have reported a general sense of fear, isolation, and stigmatization following 9/11 (Abu-Ras & Abu-Bader, 2008;Chand & Moghadam, 2004). Indeed, researchers have unequivocally demonstrated that AMIs experienced a rise in discrimination after the September 11 th attacks (Ahmed & Reddy, 2007), which was most acute in the year following the events (Kaplan, 2006).…”
Section: Microsystem Racismmentioning
confidence: 99%
“…A systematic review found only 34 articles addressing health and health behaviors among Arab Americans in the United States (El-Sayed & Galea, 2009). This paucity of research underscores the need for additional investigations, particularly given the increased incidence of discrimination and poor mental and physical health outcomes among Arab American women (Abu-Ras & Abu-Bader, 2008, 2009; Hassouneh & Kulwicki, 2007). …”
mentioning
confidence: 99%